RESULTS OF HIP REPLACEMENT WITH TUBERCULOSIS COXITIS IN PEOPLE FROM ENVIRONMENTALLY DISADVANTAGED REGIONS OF UZBEKISTAN - Rustamov, F.X.; Nazirov, P.X. (Toshkent tibbiyot akademiyasi axborotnomasi, 2020)
Intact – Compare to study the features of the course of tuberculosis coxitis and the results of hip replacement in patients from the Aral Sea regions and other regions of Uzbekistan. Materials and methods: In the clinic, the RSSPMC of Phthisiology and Pulmonoligy, the Ministry of Health of the Republic of Uzbekistan during 2013-2018, 53 operations were performed on total arthroplasty for patients with hip tuberculosis in order to study and compare the characteristics and results of hip arthroplasty in patients with devices and patients from other regions of Uzbekistan. Results: in patients from the Aral Sea region there were deep disturbances or a complete lack of joint function. The remaining patients who came from ecologically safe regions had a partial preservation of joint function with limited range of motion. Clinically, the disease was characterized by a protracted gradual onset. Output: Based on the results obtained, it can be argued that patients with tuberculosis lesions of the hip joint from ecologically disadvantaged regions of Uzbekistan have a relatively deep and extensive destructive disorder, an complicated clinical course and, correspondingly, increased recovery time.